Peran self-efficacy dan dukungan sosial teman dalam pembentukan problem-focused coping pada Kadepsin KRI di Koarmada II - Darmawan, Denny; Arya, Lutfi; Mithra (Jurnal Psikologi Poseidon, 2025)
This study examined the role of self-efficacy and peer social support in problem-focused coping among Chief Engineers (Kadepsin) of Navy Warships (KRI) in the Eastern Fleet Command (Koarmada II). The maritime work environment posed various challenges, requiring effective coping strategies. Self-efficacy, defined as an individual’s belief in their ability to overcome difficulties, and peer social support, including emotional and instrumental assistance, were assumed to contribute to managing work-related stress. A quantitative approach was employed, using a saturated sampling technique involving 72 Chief Engineers as respondents. Data were collected via Google Forms using validated scales: a 16-item self-efficacy scale (α = 0.898), a 21-item peer social support scale (α = 0.905), and a problem-focused coping scale (α = 0.940). The results showed that self-efficacy and peer social support significantly predicted problem-focused coping (R² = 0.915), accounting for 91.5% of the variance. Minor hypothesis tests revealed that self-efficacy contributed 84.6% and peer social support contributed 87.2% to problem-focused coping. These findings highlighted the importance of enhancing self-efficacy and social support networks to improve coping strategies in high-pressure maritime work environments.